(untitled) (Third Sector Social Economic Review, 2021)
The aim of the study is to investigate the effect of internet on service trade. 10 Newly Industrialized Countries (NICs) (South Africa, Mexico, Brazil, China, India, Indonesia, Malaysia, Philippines, Thailand, Turkey) include study of the 1996-2018 period. In the study, separate econometric models were created for service exports and service imports along with service trade. According to the results of the analysis made using the Fixed Effects Generalized Moments Method (FE GMM), it has a statistically significant and positive effect on internet service trade and service exports. However, a statistically significant effect of the internet on service imports could not be found. The coefficients of GDP and M2 / GDP variables used as control variables in the models were found to be statistically significant and positive. However, no statistically significant finding could be obtained regarding the real effective exchange rate variable.